CHRNG‐related nonlethal multiple pterygium syndrome: Muscle imaging pattern and clinical, histopathological, and molecular genetic findings. Issue 6 (14th March 2019) - Carrera‐García, Laura; Natera‐de Benito, Daniel; Dieterich, Klaus; de la Banda, Marta G. G.; Felter, Adrien; Inarejos, Emili; Codina, Anna; Jou, Cristina; Roldan, Monica; Palau, Francesc; Hoenicka, Janet; Pijuan, Jordi; et al.
Abstract : Mutations in the CHRNG gene cause autosomal recessive multiple pterygium syndrome (MPS). Herein we present a long‐term follow‐up of seven patients with CHRNG ‐related nonlethal MPS and we compare them with the 57 previously published patients. The objective is defining not only the clinical, histopathological, and molecular genetic characteristics, but also the type and degree of muscle involvement on whole‐body magnetic resonance imaging (WBMRI). CHRNG mutations lead to a distinctive phenotype characterized by multiple congenital contractures, pterygium, and facial dysmorphism, with a stable clinical course over the years. Postnatal abnormalities at the neuromuscular junction were observed in the muscle biopsy of these patients. WBMRI showed distinctive features different from other arthrogryposis multiple congenita. A marked muscle bulk reduction is the predominant finding, mostly affecting the spinal erector muscles and gluteus maximus. Fatty infiltration was only observed in deep paravertebral muscles and distal lower limbs. Mutations in CHRNG are mainly located at the extracellular domain of the protein. Our study contributes to further define the phenotypic spectrum of CHRNG ‐related nonlethal MPS, including muscle imaging features, which may be useful in distinguishing it from other diffuse arthrogryposis entities.